Pengaruh latihan passing variasi fun shooting game terhadap ketepatan shooting pada pemain ssb paokmotong ku 16-17 tahun - Moh zul haji al-subhi; Ali Muhaimin; Jamaludin (Yayasan Baru Haji Samsudin, 2025)
The purpose of this researcher is to determine the effect of shooting training with Passing and Move in Grid and Passing Relay Race on shooting accuracy in SSB Paokmotong KU players aged 16-17 years and to find out which is more effective. This research is an experimental research, the design used in this research is an experimental research using the design